The role of democratic parenting, school climate, and internal locus of control as predictors of academic optimism - Vivi Ratnawati; Hanggara Budi Utomo; Risaniatin Ningsih; Nora Yuniar Setyaputri (Institute of Advanced Engineering and Science, 2022)
This study examined the relationship between democratic parenting, school climate, and internal locus of control with academic optimism. This was a correlational study involving 335 students of state junior high schools who were selected using cluster random sampling technique. The data were collected by using scales of democratic parenting, school climate, internal locus of control, and academic optimism. Multiple regression technique was used to analyze the data on statistical product and service solutions (SPSS) 20. The results showed a positive and significant relationship between democratic parenting and academic optimism, school climate and academic optimism, internal locus of control and academic optimism. Besides, the result also showed that democratic parenting, school climate, internal locus of control simultaneously affected academic optimism among students. Furthermore, counseling and guidance teachers, homeroom teachers, and parents to work together to grow and improve students' academic optimism, so the students can actualize their character optimally and develop effectively.